A Systematic Review of the UAV Technology Usage in ASEAN - Adel Gohari; B. ANUAR AHMAD; Lawali Rabiu; B. A. RUZAIRI RAHIM; A.S.M. Supa'at; I. M. NASSRIN ELAMIN; M. MOHAMMED GISMALLA; Suhail Ibrahim Al-Dharrab; A. ROZEHA RASHID; Sophan Wahyudi Nawawi; Nazri Nasir; Mohd Adib Bin Sarijari; et al. (IEEE Open Journal of Vehicular Technology)
Unmanned aerial vehicles (UAVs) are emerging and have been globally incorporated in wide range of technologies for various purposes due to its advantages over conventional techniques. Nonetheless, the strength of its application areas varies globally. The aim of this paper is to systematically review the literature to provide pertinent information on UAVs’ applications among the association of southeast Asian nations (ASEAN) countries by reviewing 179 documents published from 2012 to the end of 2023. Besides, we also investigated the current state of the relevant policies and regulations among member states. The results of the research demonstrate the state of UAV adoption, application areas, popularity among member states, key aspects that are main drivers for the adoption of UAV technology in the region, and a comparison of UAV policy usage among member states. In particular, the reviewed documents highlighted 12 distinct application areas and 4 major aspects making UAV technology attractive to the region, including geographical, climatic and environmental, ecosystem conservation, and economic factors.